Historical Course of Strategies to Deal with the Prolongation of the Trial with a Focus on the Constitutional Revolution - Seyyed Hesamoddin Rafiee Tabatabaei; Abbas Pahlavanzadeh; Marzieh Afzalimehr (پژوهشهای حقوقی)
Among the various branches of the humanities in different societies, no science can be found that is not significantly influenced by the original knowledge of history and the ups and downs of the times; And the passage of time has not affected history for a long time. In the meantime, the science of law is no exception to this rule, and this knowledge and everything that belongs to it has also changed over the course of history. Legal history forms a major part of the history of civilized societies; And being aware of the evolution of any civilization also requires a correct understanding of various legal issues in the past. In order to see how the issue of delaying the trial or prolonging the process of hearing people's cases in the courts has been raised from the past to the present and what solutions have been resorted to deal with it, in this article, which is a study between the history of civilization and law, We will address this issue. Therefore, since the historical constitutional revolution became the source of important changes and developments in the Iranian legal and judicial system, we examine the issue of solutions to deal with the delay of the trial with the temporal focus of the constitutional revolution in the history of Iran.